The role of innovation potential in gaining competitive advantage in industrial companies - Sattar Kadim Hachim Almrshed (Путеводитель предпринимателя, 2020)
In today’s highly dynamic business environment, it is crucial to the growth and prosperity of a company to gain and retain a competitive advantage. Organizations need to develop unique competitive advantages to keep pace with the pace of change in technology and customer requirements. In this difficult task, organizations can benefit from innovation strategies and tools more than ever before, as they help companies improve their position in the market by increasing their performance and efficiency, and one of the strategically effective ways is to develop the innovative capabilities of a company. Our aim in this study is to clarify the role of innovative capabilities strategies in improving the performance of the organization and achieving a competitive advantage in the market. This article provides an up–to–date review of the existing literature in the field of innovation and innovative potential in order to identify the potential consequences of industrial firms gaining innovative capacity and their role in gaining a competitive advantage. This study will help managers and practitioners to understand the role of innovation management tools in gaining a competitive advantage through strategies for successfully assessing innovation potential.